Contribution of Water, Sanitation, and Hygiene Facilities to Maternal Hygiene Practices During Complementary Feeding in Ethiopia: A Systematic Review and Meta‐Analysis - Negasa Eshete Soboksa; Dinkinesh Begna Gudeta; Renay Helouise Van Wyk; Zoe Nomakhushe Nxusani; Vhushavhelo Nedzingahe; Xikombiso Gertrude Mbhenyane (Health Science Reports, 2026)
ABSTRACT Background and Aims Complementary feeding is essential for child growth and development, and good maternal hygiene practices are crucial for preventing infections. In Ethiopia, inadequate water, sanitation and hygiene (WASH) facilities can compromise food safety, increasing the risk of diarrhoea and undernutrition. This systematic review and meta‐analysis aim to evaluate the contribution of WASH facilities to maternal hygiene practices during complementary feeding in Ethiopia. Methods Relevant studies were identified through searches of PubMed, Scopus, Web of Science, JBI, the Cochrane Library, Google Scholar, and the reference lists of eligible articles. The search strategy was developed using the Population–Exposure–Outcome framework and included terms related to WASH, maternal hygiene practices, and complementary feeding in Ethiopia. Studies were screened against predefined inclusion and exclusion criteria. Data was extracted, charted, and synthesized to summarize evidence on the contribution of WASH facilities to maternal hygiene practices during complementary feeding. Results Twelve studies were included in the review. The prevalence of good maternal hygiene practices ranged from 22.2% to 62.0%. Most participants used piped or protected water sources for drinking water. Access to latrines varied from 2.4% to 96.4%, while the availability of handwashing facilities ranged from 1.4% to 64.0%. Meta‐analysis showed that mothers with access to piped or protected water sources were more likely to practise good hygiene during complementary feeding (POR = 3.41; 95% CI: 1.50‐7.78). Positive associations were also observed for access to latrines (POR = 1.70; 95% CI: 0.79–3.66) and handwashing facilities (POR = 2.20; 95% CI: 1.03–4.69). Conclusion Although the availability of WASH facilities varied across studies, the findings consistently indicated that access to safe water, sanitation, and handwashing facilities improves maternal hygiene practices during complementary feeding. Expanding WASH infrastructure and integrating hygiene education are essential to promote safer feeding practices and improve child health outcomes in Ethiopia.